How the user can influence particulate emissions from residential wood and pellet stoves: Emission factors for different fuels and burning conditions. (June 2017) - Fachinger, Friederike; Drewnick, Frank; Gieré, Reto; Borrmann, Stephan
Abstract: For a common household wood stove and a pellet stove we investigated the dependence of emission factors for various gaseous and particulate pollutants on burning phase, burning condition, and fuel. Ideal and non-ideal burning conditions (dried wood, under- and overload, small logs, logs with bark, excess air) were used. We tested 11 hardwood species (apple, ash, bangkirai, birch, beech, cherry, hickory, oak, olive, plum, sugar maple), 4 softwood species (Douglas fir, pine, spruce, spruce/fir), treated softwood, beech and oak wood briquettes, paper briquettes, brown coal, wood chips, and herbaceous species (miscanthus, Chinese silver grass) as fuel. Particle composition (black carbon, non-refractory, and some semi-refractory species) was measured continuously. Repeatability was shown to be better for the pellet stove than for the wood stove. It was shown that the user has a strong influence on wood stove emission behavior both by selection of the fuel and of the burning conditions: Combustion efficiency was found to be low at both very low and very high burn rates, and influenced particle properties such as particle number, mass, and organic content in a complex way. No marked differences were found for the emissions from different wood species. For non-woody fuels, much higher emission factors could be observed (up to five-fold increase). Strongest enhancement of emission factors was found for burning of small or dried logs (up to six-fold), and usage of excess air (two- to three-fold). Real world pellet stove emissions can be expected to be much closer to laboratory-derived emission factors than wood stove emissions, due to lower dependence on user operation. Graphical abstract: Highlights: Comprehensive dataset of emission factors for wood and pellet stoves. Real-time particle composition measurements reveal differences between burning phases. In-depth analysis of influence of burning conditions and fuels on emission factors. Sufficient residence time in combustion chamber most important to reduce emissions.